IMPLIKASI YURIDIS UU NOMOR 1 TAHUN 2023 TERHADAP PRAKTIK POLIGAMI TANPA IZIN: ANTARA KEPASTIAN HUKUM DAN PERLINDUNGAN ISTRI SAH - Mulyadi Mulyadi; Zulpahmi Lubis; Calvin Calvin (Faculty of Law, Khairun University, 2026)
Polygamy in Indonesian law is positioned as an exception to the principle of monogamy and is permitted only in a limited manner under strict requirements, including court authorization and the consent of the lawful wife. Nevertheless, unauthorized polygamous practices remain prevalent, giving rise to legal uncertainty regarding marital status and causing both material and immaterial harm to the lawful wife. This study aims to analyze the juridical implications of Law Number 1 of 2023 for unauthorized polygamy, particularly with respect to legal certainty and the protection of the lawful wife’s rights. The research employs a normative legal method with statutory, conceptual, and philosophical approaches, examining provisions of marriage law, the National Criminal Code, as well as doctrines of criminal law and Islamic law. The findings indicate that Articles 411 and 412 of the National Criminal Code provide legal certainty by affirming that the validity of marital and sexual relations is determined by recognition under state law. Unauthorized polygamy that fails to comply with family law procedures may be classified as the criminal offense of adultery or cohabitation, both of which are complaint-based offenses. This legal construction strengthens the protection of the lawful wife by positioning her as a legal subject with control over the initiation of law enforcement processes. The study concludes that the reform of the National Criminal Code is not intended to criminalize polygamy as an institution, but rather to prevent its misuse in ways that undermine the rights of the lawful wife.